NRB Food Industries Enterprise / Azlyana Azly, Farahhani Abu Talib, Fariesya Nazwa Roshidi, Mimi Nursyafiqqa Zukafli and Nurul Fateenah Afandi - Azly, Azlyana; Abu Talib, Farahhani; Roshidi, Fariesya Nazwa; Zukafli, Mimi Nursyafiqqa; Afandi, Nurul Fateenah (2019)
Palm Sugar is a sweetener derived from any variety of palm tree Palm sugar is sometimes qualified by the type of palm, as in coconut palm sugar. While sugars from different palms may have slightly different compositions, all are processed similarly and can be used interchangeably. There is various type of Gula Melaka that the company produced by different kind of users such as paste, syrup, cube and etc.